A Closer Look at the Disposition Effect in U.S. Equity Option Markets. Issue 1 (2nd January 2020) - Bergsma, Kelley; Fodor, Andy; Tedford, Emily
Abstract: The authors explore whether the disposition effect occurs in U.S. equity option markets. The disposition effect implies past winning securities will be undervalued and past losing securities will be overvalued. By adapting Grinblatt and Han's unrealized capital gains proxy to the option markets, the authors document a significant relationship between option capital gains overhang and option returns. They also find open interest decreases as option capital gains overhang increases, consistent with a disposition effect in U.S. equity options. This evidence contributes to the emerging literature on behavioral finance in derivative securities.